2021
DOI: 10.1021/acsinfecdis.0c00864
|View full text |Cite
|
Sign up to set email alerts
|

Bioluminescent Imaging Identifies Thymus, As Overlooked Colonized Organ, in a Chronic Model of Leishmania donovani Mouse Visceral Leishmaniasis

Abstract: The search for new drugs against neglected parasitic diseases has experienced a major boost in recent years with the incorporation of bioimaging techniques. Visceral leishmaniasis, the second more neglected disease in the world, has effective treatments but with several disadvantages that make the search for new therapeutic solutions an urgent task. Animal models of visceral leishmaniasis that resemble the human disease have the disadvantage of using hamsters, which are an outbred breeding animal too large to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 45 publications
0
7
0
1
Order By: Relevance
“…At 8 weeks post infection, when the chronic phase of the infection is established, groups of 5 mice were administered intraperitoneally with Salinomycin (SAL) (MedChemTronica) in 25% of DMSO at 5 mg/kg body weight (bw); paclitaxel (PXT) (Teva) in 0.154 M NaCl at 22.5 mg/kg bw or docetaxel (DXT) (Taxotere, Sanofi) in 0.9% NaCl at 6 mg/kg bw once a day for 10 days. Nifuratel (NFT) (MedChemTronica), diluted in 0.75% carboxymethyl cellulose (Sigma-Aldrich), was administered by oral gavage at 50 mg/kg bw once or twice a day for 10 days . Oral miltefosine (Sigma-Aldrich) at 40 mg/kg bw once a day for 5 days, was used as control.…”
Section: Methodsmentioning
confidence: 99%
“…At 8 weeks post infection, when the chronic phase of the infection is established, groups of 5 mice were administered intraperitoneally with Salinomycin (SAL) (MedChemTronica) in 25% of DMSO at 5 mg/kg body weight (bw); paclitaxel (PXT) (Teva) in 0.154 M NaCl at 22.5 mg/kg bw or docetaxel (DXT) (Taxotere, Sanofi) in 0.9% NaCl at 6 mg/kg bw once a day for 10 days. Nifuratel (NFT) (MedChemTronica), diluted in 0.75% carboxymethyl cellulose (Sigma-Aldrich), was administered by oral gavage at 50 mg/kg bw once or twice a day for 10 days . Oral miltefosine (Sigma-Aldrich) at 40 mg/kg bw once a day for 5 days, was used as control.…”
Section: Methodsmentioning
confidence: 99%
“…With the introduction of bioluminescent mouse models of visceral leishmaniasis, it has become easier to track infection; this could potentially be used longitudinally to track the location of parasites as the disease develops. For example, in a recent study 46 it was reported that the thymus, a lymphatic organ, seems to be infected from the beginning until the late phases of the infection.…”
Section: Improved Understanding Of Parasite Biologymentioning
confidence: 99%
“…Interestingly, it was possible to observe many more intact amastigotes in the undernourished animals than in the well-nourished ones ( 70 ). Recent reports have confirmed, using bioluminescence, the presence of the parasite in the thymus of well-nourished BALB/c mice infected with L. donovani ( 71 ). These observations demonstrate that the thymus is a target organ during infection by viscerotropic species of Leishmania , including L. infantum and L. donovani .…”
Section: Undernutrition Yields a Further Negative Impact Of Acute Inf...mentioning
confidence: 78%